Decision circuit and bit error rate estimation for absolute polar duty cycle division multiplexing - Malekmohammadi, A.; Abdullah, M.K.; Mahdiraji, Ghafour Amouzad; Abas, A.F.; Mokhtar, M.; Rasid, M.F.A.; Basir, S.M. (Praise Worthy Prize, 2008)
A novel concepts of decision circuit and Bit-error-rate (BER) estimation method for Absolute Polar Duty Cycle Division Multiplexing (AP-DCDM) is proposed The concepts have significant differences to those used in conventional microwave communication receivers. This is due to the unique characteristics of the multilevel signal produced in AP-DCDM system. The BER estimation method is validated by simulation and compared against bit-to-bit comparison method.